2015
DOI: 10.5152/ejp.2014.89106
|View full text |Cite
|
Sign up to set email alerts
|

Smear-Negative Pulmonary Tuberculosis

Abstract: Tuberculosis (TB) is the second leading cause of death from an infectious disease worldwide, after the human immunodeficiency virus. There are almost 2.5 million new smear-positive pulmonary TB cases and 1.9 million new smear-negative pulmonary TB cases in the world in 2012 according to the World Health Organization (WHO) Global Tuberculosis Report 2013. Smear negativity in pulmonary TB is a common clinical problem. Clinicians have difficulty in diagnosing smear-negative pulmonary TB without bacteriological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Although the microscopic investigation is the fastest diagnostic method, the performance of sensitivity is relatively low. 20 In our study, only 40% of the TB-HIV group had positive smear results, meanwhile, the urinary Mtb antigen cocktail test result in this group was 93.3%. Our previous study mentioned the added value of urinary Mtb antigen cocktail, we found the sensitivity of AFB staining was 45.4% to 90% when combined with urinary Mtb antigen cocktail assay.…”
Section: Discussioncontrasting
confidence: 47%
“…Although the microscopic investigation is the fastest diagnostic method, the performance of sensitivity is relatively low. 20 In our study, only 40% of the TB-HIV group had positive smear results, meanwhile, the urinary Mtb antigen cocktail test result in this group was 93.3%. Our previous study mentioned the added value of urinary Mtb antigen cocktail, we found the sensitivity of AFB staining was 45.4% to 90% when combined with urinary Mtb antigen cocktail assay.…”
Section: Discussioncontrasting
confidence: 47%
“…Although the microscopic investigation is the fastest diagnostic method, the performance of sensitivity is relatively low. For a positive result, samples must contain more than 10.000 bacilli per milliliter [ 5 ]. This is shown in our study for the performance of AFB stain against mycobacterial culture, as high as 45.4% for sensitivity and 67% for specificity.…”
Section: Discussionmentioning
confidence: 99%
“…First, mycobacterial culture is still the reference standard method for pulmonary tuberculosis diagnosis. The culture needs the presence of 10–100 bacilli in a milliliter of the sample to obtain the culture sensitivity of 81.5% and the specificity of 98.4% [ 5 ]. This shows that culture positivity depends on the number of bacilli in a milliliter of sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation